Micro ARcade - Wong, Renee Tong Ling (Nanyang Technological University, 2023)
The evident increase of microplastics poses a serious threat to our future as it displays harmful effects on the environment and in us. Micro ARcade aims to educate players on the existence of these pollutants and how they can affect an ecosystem. Drawing on the powers of augmented reality, Micro ARcade speculates how players can view nature at a microscopic level. Revealing the struggle against microplastics that would otherwise be invisible to the naked eye. Players are set to eliminate the microplastics by eating them, adding a sense of urgency as the digital ecosystem is affected by the presence of microplastics in the scene. This project also aims to explore the importance of adding physicality to digital games, to ground the players in reality. Setting the digital ecosystem on a physical open terrarium allows players to explore and interact with their surroundings in an immersive way, while adding a layer of materiality to a very tangible problem. Micro ARcade hopes to inspire a deeper connection and appreciation for nature through a ‘phygital’ (physical and digital) experience.